A Phenomenological Study of Representations of a Person with Down Syndrome in “Le huitième jour” by Jac van Dormael - Jakaitė, Dalia (Sociologija. Mintis ir veiksmas, 2021)
The subject of the article is the world of a person with an intellectual disability in the comedy drama of Belgian director Jac von Dormael “Le huitième jour” (1996, “The Eighth Day”). The purpose of the article is phenomenological reading and analysis of the representation of a person with Down syndrome and his living world in the featured film, focusing on the emotional and social representation of the disability phenomenon. The approach of the filmmakers to the issue of disability is examined with the principles of social and film phenomenology, semantics and poetics of the artistic text. The research focuses on two perspectives of the phenomenon: a) the relationship of the main character Georges – a musical, theatrical, positive young man with Down syndrome – with his closest family and b) his dialogue with the wider society, which mainly emerges from the communication with Harry – the family father and a successful career teacher. The article makes analytical conclusions about emotional-social phenomena and their significance for the concept of disability, discussing other feature films of a similar period in the comparison. The research invites us to delve deeper into the representation of the experiences of joy and pain that is characteristic of the film “The Eighth Day” and at the same time provokes broader cultural associations.